2019
DOI: 10.3390/w11091823
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Flow Parameters through Subsurface Drainage Modules for Application in BIOECODS

Abstract: The flow resistance of the existing modules in the bio-ecological drainage system (BIOECODS) is high and may lead to flood instead of its mitigation. As part of efforts to enhance the performance of the system, the river engineering and urban drainage research center (REDAC) module was developed. This study modelled the hydrodynamics of flow through this module using FLOW-3D and laboratory experiments for two cases of free flow without module (FFWM) and flow with a module (FWM) to understand and visualize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…4 the car model dragged from its original location and sliding failure mode was noticed. The numerical results were compared with Australiana rainfall and runoff guidelines (2011) [32] and good agreement was noticed as shown in Figure 18. From the results it can be concluded that, numerical simulation using FLOW-3D can give good predictions and results related to vehicle instability limits.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…4 the car model dragged from its original location and sliding failure mode was noticed. The numerical results were compared with Australiana rainfall and runoff guidelines (2011) [32] and good agreement was noticed as shown in Figure 18. From the results it can be concluded that, numerical simulation using FLOW-3D can give good predictions and results related to vehicle instability limits.…”
Section: Resultsmentioning
confidence: 73%
“…FLOW-3D is a commercial code which uses finite volume method (FVM) and turbulence models to solve continuity and Navier stokes equations [31,32]. The FLOW-3D software also allow the numerical simulation under six degree of freedom which can represent the real experiment condition [28].…”
Section: Methodsmentioning
confidence: 99%
“…Before conducting the numerical simulation, mesh quality was checked using Fractional Area/Volume Obstacle Representation (FAVOR) solver. The FAVOR solver is a unique tool which can be used to check the mesh quality and confirm whether the geometry was accurately captured [26]. Based on the FAVOR solver outcomes, it was found out that the selected cell sizes can capture all model geometries perfectly.…”
Section: Materials Characteristics and Specificationsmentioning
confidence: 99%
“…SDM is a water infiltration storage tank for stormwater control and management, and it is also known as the Modular Rainwater. The main purpose of the modular tank is to allow natural water infiltration on-site, which reduces surface runoff [32]. However, in this study, the SDM was used as an additional layer of the saturated zone creating an anaerobic condition to enhance nutrient removal by increasing retention time and promoting more biological removal processes.…”
Section: Cascaded Bioretention Setupmentioning
confidence: 99%